A Influence of Reservoir Water Level Fluctuations of Reservoir B (Rusunawa) on Groundwater Availability at the Environment of Lampung University: English - Erwanto, Erwanto (Faculty of Engineering, Universitas Lampung Jl. Soemantri Brojonegoro No.1 Bandar Lampung, Indonesia 35141, 2023)
The presence of four reservoirs as rainwater collection infrastructure at the University of Lampung is expected to enhance the infiltration process and recharge the groundwater aquifers. However, the threat of water scarcity in the area may arise due to the reduction of recharge areas. Therefore, a comprehensive study is necessary to understand the important factors in maintaining groundwater availability. This research aims to analyze groundwater aquifers, identify fluctuations in the water level of Reservoir B, and analyze the relationship between the elevation of the water level in the reservoir and the availability of groundwater in the University of Lampung environment. The research methodology involves the interpretation of geoelectric data and the calculation of water level fluctuations in the reservoir. The analysis results indicate that the shallow groundwater aquifer is estimated to be located at depths ranging from 10 to 30 meters, while the deeper aquifer is situated at depths of 80 to 130 meters with a layer of sandy tuff. The highest fluctuation in water level is recorded at 14 cm during rainfall with an intensity of 52.1 mm/day. There were no significant changes in the water level observed during rainfall with intensities ranging from 0 to 2.4 mm/day, and the average fluctuation observed is approximately 0.5 cm every 8 hours.